1995
DOI: 10.1016/s0022-0736(95)80001-8
|View full text |Cite
|
Sign up to set email alerts
|

Mechanisms of defibrillation

Abstract: Electrical shock has been the one effective treatment for ventricular fibrillation for several decades. With the advancement of electrical and optical mapping techniques, histology, and computer modeling, the mechanisms responsible for defibrillation are now coming to light. In this review, we discuss recent work that demonstrates the various mechanisms responsible for defibrillation. On the cellular level, membrane depolarization and electroporation affect defibrillation outcome. Cell bundles and collagenous … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
5
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
2
1

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 30 publications
0
5
0
Order By: Relevance
“…When a threshold is reached, the action potential is triggered and thus cell contraction takes place. [ 45 ] In cardiac tissues, however, the description of this phenomenon is more complex due to the heterogeneity of the tissue and the presence of cellular gap junctions that electrically couple the cells that populate the tissue and alter signal propagation. The details of this phenomenon have been reviewed elsewhere in more depth.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…When a threshold is reached, the action potential is triggered and thus cell contraction takes place. [ 45 ] In cardiac tissues, however, the description of this phenomenon is more complex due to the heterogeneity of the tissue and the presence of cellular gap junctions that electrically couple the cells that populate the tissue and alter signal propagation. The details of this phenomenon have been reviewed elsewhere in more depth.…”
Section: Resultsmentioning
confidence: 99%
“…The details of this phenomenon have been reviewed elsewhere in more depth. [ 45 ] Briefly, cells near the electrodes depolarize and trigger an action potential that propagates along the tissue due to the presence of gap junctions in the cells.…”
Section: Resultsmentioning
confidence: 99%
“…When a threshold is reached, the action potential is triggered and thus cell contraction takes place. [46] In cardiac tissues, however, the description of this phenomenon is more complex due to the heterogeneity of the tissue and the presence of cellular gap junctions that electrically couple the cells that populate the tissue and alter signal propagation. The details of this phenomenon has been reviewed elsewhere in more depth.…”
Section: Electrical Stimulation Of Cardiac Microtissues Using An E-lid With 3d-printed Pyrolyzed Carbon Electrodesmentioning
confidence: 99%
“…The details of this phenomenon has been reviewed elsewhere in more depth. [46] Briefly, cells near the electrodes depolarize and trigger an action potential that propagates along the tissue due to the presence of gap junctions in the cells. In order to determine the excitation threshold (ET), i.e., the minimum potential difference required to elicit a tissue contraction, we progressively increased the potential difference between the electrodes from 10 mV up to 350 mV.…”
Section: Electrical Stimulation Of Cardiac Microtissues Using An E-lid With 3d-printed Pyrolyzed Carbon Electrodesmentioning
confidence: 99%
“…These considerations led to the ULV hypothesis, which states that for a shock to successfully terminate VF, it must alter the transmembrane potential throughout the myocardium in such a way that the wavefronts of VF are halted, yet new wavefronts that can reinitiate VF are not induced (69). These realizations led to the development of the critical point theory of defibrillation, which suggested that reentry was initiated at the intersection of critical points of local field strength and tissue with critical levels of recovery (68, 71). …”
Section: Global Mechanisms Of Defibrillationmentioning
confidence: 99%